2017
DOI: 10.1021/acs.cgd.7b01159
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of ZnGa2O4: A New, Deep Ultraviolet Semiconductor Candidate

Abstract: ZnGaO films were grown on c-plane sapphire substrates by metal organic chemical vapor deposition using diethylzinc (DEZn), triethylgallium (TEGa), and oxygen. The flow rate of DEZn was 10–60 sccm, and those of TEGa and oxygen were held constant. The ZnGaO film prepared at a DEZn flow rate of 10 sccm adopted a (2̅01)-oriented single-crystalline β-Ga2O3 phase, whereas those prepared at 30–60 sccm exhibited a (111)-oriented single-crystalline ZnGa2O4 phase. On the basis of Hall measurements, ZnGaO films (10 sccm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…Post-annealing affected the crystalline quality, surface properties, altered defects, and electrical properties of ZnGa 2 O 4 films. Our previous studies have demonstrated the quality of as-grown ZnGa 2 O 4 films, which contain lower degree of crystallinity and higher point defects than those of annealed ZnGa 2 O 4 films 11 . The dark current of as-grown ZnGa 2 O 4 film PDs (Idark ~1 mA at a 20 V bias) was approximately 10 8 times higher than that of annealed PDs based on ZnGa 2 O 4 films so that the photocurrent stimulated by DUV light was difficult to distinguish.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Post-annealing affected the crystalline quality, surface properties, altered defects, and electrical properties of ZnGa 2 O 4 films. Our previous studies have demonstrated the quality of as-grown ZnGa 2 O 4 films, which contain lower degree of crystallinity and higher point defects than those of annealed ZnGa 2 O 4 films 11 . The dark current of as-grown ZnGa 2 O 4 film PDs (Idark ~1 mA at a 20 V bias) was approximately 10 8 times higher than that of annealed PDs based on ZnGa 2 O 4 films so that the photocurrent stimulated by DUV light was difficult to distinguish.…”
Section: Resultsmentioning
confidence: 94%
“…The flow rates of DEZn, TEGa, and oxygen were maintained at 40, 50, and 200 sccm, respectively. Previously, we have systematically investigated in details the effects of different growth parameters on the successfully grown (111)-oriented single-crystalline ZnGa 2 O 4 films by MOCVD technique 11 . The as-grown epilayer was subsequently annealed in the furnace for 1 h at 700, 800 and 900 °C in nitrogen ambient.…”
Section: Experimental Methods and Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnGa 2 O 4 materials have recently gained increased attention [2,3]. These materials are widely applied in vacuum fluorescent and field emission displays, gas sensors, electronic devices, and solar-blind ultraviolet photodetectors (PDs) due to their high transparency in the deep ultraviolet (DUV) spectral region, excellent thermal and chemical stability, and wide optical band gap (~5 eV) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…ZnGa 2 O 4 phosphor materials have been prepared by several methods, including radio-frequency (RF) magnetron sputtering [6], sol-gel processing [7], metal organic chemical vapor deposition (MOCVD) [8] and pulsed laser deposition [9]. However, they are mostly used to conduct synthesis of one-dimensional nanostructures (nanoparticles, nanowires and nanotubes) and are known to improve the emission characteristics of ZnGa 2 O 4 phosphor powder [10][11][12].…”
Section: Introductionmentioning
confidence: 99%